2006
DOI: 10.2166/wst.2006.305
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and assessment of oil pollution in the Danube River during the transnational Joint Danube Survey

Abstract: An extensive river basin monitoring exercise of 2581 km of the river Danube was carried out in 2001 under of the aegis of the transnational Joint Danube Survey (JDS). Water, suspended and bottom sediment, and biota samples were collected from 76 cross-sections in the Danube main stream and 22 major tributaries during the 39-day cruise, and analysed for chemical and biological variables. During the JDS, oil pollution was characterised with GC-FID and fluorescence measurements. Fluorescence fingerprints of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The most considered topics were pollution with: metals in the water 4-7 and sediments, [8][9][10][11] nutrients, [12][13][14][15][16][17] radioisotopes, [18][19][20] oil, 21 etc. There are many studies dealing with the general pollution status of the river, hence covering more than one group of pollutants [22][23][24][25] and also from a regulatory point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The most considered topics were pollution with: metals in the water 4-7 and sediments, [8][9][10][11] nutrients, [12][13][14][15][16][17] radioisotopes, [18][19][20] oil, 21 etc. There are many studies dealing with the general pollution status of the river, hence covering more than one group of pollutants [22][23][24][25] and also from a regulatory point of view.…”
Section: Introductionmentioning
confidence: 99%
“…During JDS1 (Literáthy et al 2002), a total of 49 aquatic macrophyte species was identified, including 14 species of mosses, 16 submerged, nine floating leaf and free-floating plant species, as well three helophytes and one Characeae species. In the Upper Danube, bryophytes (mosses) dominate (67-89% cover).…”
Section: Riparian and Aquatic Plantsmentioning
confidence: 99%
“…Insects make up 74% of the total aquatic species biodiversity in the Danube (Graf et al 2015). The macroinvertebrate fauna of the Danube is highly diverse (Russev 1998, Literáthy et al 2002, Slobodník et al 2005, Csányi and Paunovič 2006. This is a consequence of strong longitudinal and lateral hydrogeomorphic gradients (Literáthy et al 2002, Sommerhäuser et al 2003.…”
Section: Macroinvertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most exploited topics were pollution with: metals in water (Madarasz and Horvath 2001;Dumbrava et al 2008;Guieu and Martin 2002;Dumbrava and Birghila 2009) and sediments (Milenković et al 2005;Enache 2008;Crnković et al 2008;Oresčanin et al 2005;Relić et al 2010), nutrients Teodoru and Wehrli 2005;Schreiber et al 2005;Behrendt et al 2005;Kalchev et al 2008;Lair et al 2009), radioisotopes (Vuković et al 2006;Miljević et al 2008;Krmar et al 2009), oil (Literathy 2006) etc. There are many studies dealing with the general pollution status of the river, covering more than one group of pollutants (Vogel 2003;Galatchi and Vladimir 2006;Pawellek et al 2002;Kundev et al 2001) as well as from the regulatory point of view (Avis and Weller 2000).…”
Section: Introductionmentioning
confidence: 99%